A Compatibility Law and the Classification of Theory Change - Patrick Thomas Fraser; Ameer Sarwar (Scientonomy, 2018)
The current formulation of the zeroth law (the law of compatibility) is marred with a number of theoretical problems, which necessitate its reformulation. In this paper, we propose that compatibility is an independent stance that can be taken towards epistemic elements of all types. We then provide a new definition of compatibility criteria to reflect this change. We show that the content of the zeroth law is deducible from our definition of compatibility. Instead of a static law of compatibility, we propose a new dynamic law of compatibility that explains how the stance of compatibility obtains. Unlike the zeroth law, this new law has empirical content, as it forbids certain conceivable scenarios. Having established these notions, we propose a classification space that exhaustively covers all the possible states a theory may occupy and all the transitions it may undergo during its lifecycle.